REALISASI KONTRAK KERJA KONSTRUKSI PIHAK SWASTA DENGAN DINAS PERUMAHAN RAKYAT DAN KAWASAN PERMUKIMAN SERTA PERTANAHAN - Devinia Yuri Safira; Sri Maharani (LPPM Universitas Ekasakti Padang, 2023)
Infrastructure development by the government, namely the Surabaya People's Housing and Settlement Area and Land Affairs Office, is carried out by holding project tenders to cooperate with private parties engaged in construction services to expedite the development process. This study aims to determine the implementation of construction work contracts between the parties, especially when there is default and the type of research used is empirical juridical. The results of the study show that it is the competence side of human resources from the private sector that is the factor causing defaults in the implementation of construction work contracts. Handling from the agency is carried out by holding an addendum which simultaneously gives a warning, imposes fines, and blacklists private companies. Obstacles that occur in the handling process come from the internal side, namely the private sector that is not cooperative. In addition, it also came from the external side, namely from the private sector engaged in construction services. Solutions to dealing with these obstacles require upholding legal certainty as well as revamping the system in its implementation to make it more stringent and prevent things that end up causing harm to many parties in the development process.